2021
DOI: 10.47470/0016-9900-2021-100-3-279-284
|View full text |Cite
|
Sign up to set email alerts
|

Risks of developing diseases of an eye and its adnexa in students in conditions of the violation of hygienic rules for the use of electronic devices

Abstract: Introduction. The process of involving children, adolescents and youth in the constantly developing information space is an objective reality. At the same time, the lack of monitored indices of the safety of electronic devices (ED) for the health of children and adolescents, the lack of a clearly built system of preventive measures require its development and improvement, which will reduce the risk of the digital information environment impact on the health of the younger generation. Materials and methods. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 19 publications
0
0
0
2
Order By: Relevance
“…Электронные средства обучения способствуют повышению зрительной концентрации, существенно увеличивая длительность работы органа зрения. В ряде научных публикаций, касающихся эргономики в связи с электронными устройствами, в основном акцентируется внимание на гигиене зрительной работы [15][16][17][18]. В ранее проведенных исследованиях показано возникновение ряда жалоб на нарушение самочувствия; общее и зрительное утомление школьников и при использовании интерактивных панелей на уроке [19].…”
unclassified
“…Электронные средства обучения способствуют повышению зрительной концентрации, существенно увеличивая длительность работы органа зрения. В ряде научных публикаций, касающихся эргономики в связи с электронными устройствами, в основном акцентируется внимание на гигиене зрительной работы [15][16][17][18]. В ранее проведенных исследованиях показано возникновение ряда жалоб на нарушение самочувствия; общее и зрительное утомление школьников и при использовании интерактивных панелей на уроке [19].…”
unclassified
“…По данным научных работ, негативное воздействие социально-экономических факторов, окружающей среды, организации образовательного процесса способствует формированию дополнительных случаев заболеваний, включая болезни глаза [1,6,7]. Среди факторов риска, способствующих формированию нарушений рефракции и аккомодации, одно из ведущих мест принадлежит нерациональному использованию педагогами в учебном процессе и бесконтрольному самостоятельному применению детьми смартфонов и других электронных устройств [8][9][10].…”
unclassified
“…Electronic learning aids increase visual concentration, significantly prolonging a period during which the eyes have to work. In several scientific publications concerning ergonomics in connection with electronic devices, attention is mainly focused on the hygiene of visual work [15][16][17][18]. Previous studies have reported several complaints about health deterioration; general and visual fatigue of schoolchildren when using interactive panels in classes [19].…”
mentioning
confidence: 99%